Pelagomanes thaumasia, n. comb. - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Zenodo, 2022)
Pelagomanes thaumasia (Caulet, 1991) n. comb. Plate 39, Figs. 10A –11. Lophophaena? thaumasia n. sp., Caulet, 1991, pl. 2, figs. 5–6. Lophophaena? thaumasia Caulet, Renaudie, 2014, pl. 33, fig. 4. Lithomelissa? kozoi cf sp 4 (partim), Trubovitz et al., 2020, supplementary data 7. Remarks. P. thaumasia has a strong tribladed apical horn, which differentiates it from P. kozoi (Pl. 39, Figs. 1–6) and P. stigi (Pl. 39, Figs. 7–9). It has randomly arranged pores on the thorax, which do not align along ribs, as in P. morawanensis (Pl. 40, Figs. 4A – 6, 9, 11–12) and P. cantharoides (Pl. 40, Figs. 1–3, 7–8, 10, 14). This species lacks strong ribs and prominent teeth at the base of the thorax. The specimens observed in the EEP appear to have a slightly more narrow thorax than those observed by Renaudie in the Southern Ocean, and those figured by Caulet (1991). Range. Middle Miocene—Pleistocene in the EEP (Table 1). Published as part of Trubovitz, Sarah, Renaudie, Johan, Lazarus, David & Noble, Paula, 2022, Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific, pp. 1-158 in Zootaxa 5160 (1) on page 83, DOI:10.11646/zootaxa.5160.1.1, http://zenodo.org/record/10544058